2011
DOI: 10.1016/j.pneurobio.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The pain matrix reloaded

Abstract: (word count: 247)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
319
1
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 729 publications
(354 citation statements)
references
References 170 publications
(220 reference statements)
22
319
1
12
Order By: Relevance
“…[7]). Hence, rather than representing the other's affect, activation of these areas might stem from the phenomenon that seeing someone in a painful situation is a strong and salient social cue arousing the observer, and preparing him or her to respond to a potential threat.…”
Section: From Shared Activations To Shared Representationsmentioning
confidence: 99%
“…[7]). Hence, rather than representing the other's affect, activation of these areas might stem from the phenomenon that seeing someone in a painful situation is a strong and salient social cue arousing the observer, and preparing him or her to respond to a potential threat.…”
Section: From Shared Activations To Shared Representationsmentioning
confidence: 99%
“…Acute physical pain is known to spark specific and complex physiological responses, evinced by increased skin conductance, faster heart rate, and higher levels of blood cortisol, adrenaline and noradrenaline, heralding pain-activation of the hypothalamic-pituitary-adrenal axis and the sympathetic nervous system (Benarroch & Sandroni, 2005;Pacák & McCarty, 2000). Neuroimaging studies show pain is associated with activity in an extensive subcortical and cortical network, referred to as the pain matrix (Legrain, Iannetti, Plaghki, & Mouraux, 2011;Melzack, 1999Melzack, , 2005. This network integrates ascending signals and modulates descending feedback, and includes the dorsal anterior cingulate cortex, insula, periaqueductal grey, primary somatosensory cortex and prefrontal cortex (C. R. Chapman, 2005;Coghill, McHaffie, & Yen, 2003;Eisenberger, 2012c;Tracey, 2010).…”
Section: Biological Mechanismmentioning
confidence: 99%
“…They suggested that the observed patterns of activation might not be exclusive to social or physical pain experiences but rather to multiple salient categories of stimuli, for instance, stimuli broadly pertaining to threat (see also Legrain et al, 2011). Furthermore, Iannetti et al (2013) raised the possibility that perceptual differences in the experiences of social and physical pain could be better characterised with novel neuroimaging analysis techniques (e.g., .…”
Section: What Is Pain? 'Hurt Feelings' and Feeling Hurtmentioning
confidence: 99%
See 2 more Smart Citations